2001
DOI: 10.1046/j.0269-8463.2001.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Gape size allometry in pike reflects variation between lakes in prey availability and relative body depth

Abstract: Summary 1.The gape size of the predator and the body depth of its prey are the main factors deciding whether a gape-limited piscivore can ingest a potential prey fish. The connection between morphological variation in pike and its prey was studied in five lakes with different proportions of pike, perch and roach. 2. At low prey abundance the prey fish are larger than in lakes with a higher prey density. In contrast, the pike are smaller but have relatively high gapes in the lake with the lowest prey availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
69
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 39 publications
2
69
0
1
Order By: Relevance
“…This pattern is similar to that found in northern pike, Esox lucius L. where the mouth size was correlated with body length on different lakes in Sweden (Magnhagen and Heibo 2001). Between different species, the variation in size of the feeding apparatus is commonly explained as an adaptation to the type of prey to enhance the ability of the predator to capture and ingest its prey.…”
Section: Discussionsupporting
confidence: 84%
“…This pattern is similar to that found in northern pike, Esox lucius L. where the mouth size was correlated with body length on different lakes in Sweden (Magnhagen and Heibo 2001). Between different species, the variation in size of the feeding apparatus is commonly explained as an adaptation to the type of prey to enhance the ability of the predator to capture and ingest its prey.…”
Section: Discussionsupporting
confidence: 84%
“…Mouth size is one of the most important factors determining foraging ability and consequently fish diet (Breck, 1993 ;Magnhagen and Heibo, 2001). Karpouzi and Stergiou (2003) have shown that bogue possesses the smallest mouth dimensions among 18 Mediterranean species (including a group of 12 omnivorous species).…”
Section: Discussionmentioning
confidence: 99%
“…Nilsson and Brönmark (2000) found that gape size was linearly related to total body length in pike population. Magnhagen and Heibo (2001) reported that the size of gape increased with total body length in pike samples. The prey body height (PBH) changed as a function of vertical and horizontal mouth gape in Lake Ladik.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical significance of selection index value (V a ) was tested using the chisquared test (χ2-test). Values without subscripts are expressed as: (Magnhagen & Heibo, 2001;Dörner et al, 2003) were calculated using linear regression analysis. One-way analysis of the variance (ANOVA) was used to test the statistical significance of linear regression (Czerwinski et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation